Paleobiogeographical origins of Fasciola hepatica and F. gigantica in light of new DNA sequence characteristics of F. nyanzae from hippopotamus - Bargues, María Dolores; Halajian, Ali; Artigas, Patricio; Luus-Powell, Wilmien J.; Valero, M. Adela; Mas-Coma, Santiago (Frontiers in Veterinary Science, 2022)
Fascioliasis is a highly pathogenic disease affecting humans and livestock worldwide. It is caused by the liver flukes Fasciola hepatica transmitted by Galba/Fossaria lymnaeid snails in Europe, Asia, Africa, the Americas and Oceania, and F. gigantica transmitted by Radix lymnaeids in Africa and Asia. An evident founder effect appears in genetic studies as the consequence of their spread by human-guided movements of domestic ruminants, equines and Old World camelids in the post-domestication period from the beginning of the Neolithic. Establishing the geographical origins of fasciolid expansion is multidisciplinary crucial for disease assessment. Sequencing of selected nuclear ribosomal and mitochondrial DNA markers of F. nyanzae infecting hippopotamuses (Hippopotamus amphibius) in South Africa and their comparative analyses with F. hepatica and F. gigantica, and the two Fascioloides species, Fs. jacksoni from Asian elephants and Fs. magna from Holarctic cervids, allow to draw a tuned-up evolutionary scenario during the pre-domestication period. Close sequence similarities indicate a direct derivation of F. hepatica and F. gigantica from F. nyanzae by speciation after host capture phenomena. Phylogenetic reconstruction, genetic distances and divergence estimates fully fit fossil knowledge, past interconnecting bridges between continents, present fasciolid infection in the wild fauna, and lymnaeid distribution. The paleobiogeographical analyses suggest an origin for F. gigantica by transfer from primitive hippopotamuses to grazing bovid ancestors of Reduncinae, Bovinae and Alcelaphinae, by keeping the same vector Radix natalensis in warm lowlands of southeastern Africa in the mid-Miocene, around 13.5 mya. The origin of F. hepatica should have occurred after capture from primitive, less amphibious Hexaprotodon hippopotamuses to mid-sized ovicaprines as the wild bezoar Capra aegagrus and the wild mouflon Ovis gmelini, and from R. natalensis to Galba truncatula in cooler areas and mountainous foothills of Asian Near East in the latest Miocene to Early Pliocene, around 6.0 to 4.0 mya and perhaps shortly afterwards.